Collection, morphological characterization, bioactivity evaluation and micropropagation of selected Tacca Species (Dioscoreaceae) - Misrol, Mohd Zulhilmi (2016)
Studies were carried out with the objectives of establishing a germplasm collection of selected Tacca species from various accessions in Malaysia, to describe the morphological characters of selected Tacca species, to evaluate anti-cancer, antihistamine and anti-inflammatory activity using various parts of plant crude extract and to improve and develop tissue culture protocol for T.integrifolia. Tacca (Dioscoreaceae) is a native understorey medicinal plant with a great potential to be developed as an ornamental plant and is considered rare in Malaysia. A germplasm collection consisting of 60 samples representing four species from three states of Peninsular Malaysia and one of Sarawak was established in Field 2 of the University Farm, UPM. Tacca species was found growing under various environment conditions where T. integrifolia, T. chantrieri and T .nivea thrived on the moist soils of the forest floor in well-drained areas, high humidty and under more than 70% shade. In contrast, T. leontopetaloides was found in dappled shade under coconut trees and under full sun (0% shade) along coastal areas. The conserved Tacca species has been characterized for important vegetative and morphological characters for utilization as an ornamental and medicinal plant. The most variation among Tacca species differed in their seed shape, apices of innermost bracts, bract and bracteoles color. The bract and bracteoles color were purple color in Tacca integrifolia, dark purple color in Tacca chantrieri, white purplish in Tacca nivea and green color in Tacca leontopetaloides.Three different groups were determined from group cluster and dendrogram based on 23 qualitative and 12 quantitative characteristics among Tacca species using MVSP programme. Various plant parts of selected Tacca species [Tacca integrifolia (TI), Tacca chantrieri (TC) and Tacca nivea (TN)] were extracted and tested for their in vitro cytotoxicty in cancer cell lines using MTT assay. Results obtained showed that the rhizome extracts were the most potent among the various parts of the plants. Among the rhizome extracts, TI showed the most promising anti-tumour activity, followed by TN and TC. Further investigation on TI revealed that HCT116 and PC-3 cells were the most sensitive towards the rhizome extracts, with GI50 values of 3.3 ± 1.3 μg/mL and 4.0 ± 0.8 μg/mL respectively. In conclusion, the rhizome extract of TI emerged as the most potent and further study on the plant is warranted. Antihistamine and nitric oxide (NO) inhibitory activity were carried out using methanolic extract from various plant parts (PPCE) and selected Tacca species (TSCE). The antihistamine activity was tested in rat mast cell (RBL-2H3) line. Results obtained shows mild antihistamine activity among PPCE and TSCE without showing cytotoxicity activity on RBL-2H3 cells after 4 h using MTT assay. The NO inhibitory activity was determined in a murin macrophage cell line (RAW 264.7). The results demonstrated weak NO inhibitory activity by T. integrifolia rhizome extract (TIR) compared with others TSCE and PPCE. Cell exposed to the extracts showed viability with a range of 60 to 90%. The sterile seeds for the propagation of sterile seedlings were prepared by surface sterilization of loose seed (LS) in 10% commercial bleach, CLOROX and aseptic removal of sterile seeds from fruits pre-sterilized (FS) by burning using 95% ethanol. The sterile seeds from both sources were cultured on the sterile ½ MS and full MS media containing 30 g/L sucrose, pH 5.6 for 4 months. The highest percentage of germination of T.integrifolia seeds were recorded from LS in ½ MS media (56%), follow by FS with ½ MS media (16%), LS with full MS (10%) and FS with full MS media (8%) after four months of cultured. The effect of in vitro vertical cutting and decapitation on efficient shoot multiplication of T. integrifolia was investigated via shoot tip in MS medium and MS medium fortified with 1 mg/L of 6-benzylaminopurine (BAP). In vitro seedlings (2 to 4 cm in height) were cut directly by vertical and decapitated 0.5-0.7 cm above from cotyledon node. After 12 weeks of culture, plantlets regenerated from decapitation in MS medium fortified with 1 mg/L BAP were able to produce new healthy shoots higher than intact and vertical cutting plantlet in the same medium. The protocol for in vitro propagation of T. integrifolia through shoot was carried out. The shoot derived from sterile seedling was used as explants for shoot induction and multiplication. The explants were harvested from 16 weeks old seedling and cultured on solidified MS medium supplemented with various concentration of BAP (0, 1, 2, 3, 4, 5 mg/L) for shoot induction and multiplication. The highest number of new shoots and leaves were obtained in MS medium supplemented with 3 mg/l BAP. MS medium with 0.3 mg/L IBA was recommended for root induction after eight weeks of culture with highest number of healthier root.